Inventory and internal logistics management as critical factors affecting the supply chain performances. (10th April 2010) - Curcio, Duilio; Longo, Francesco
This paper focuses on the inventory and internal logistics management problem within a specific Supply Chain (SC) node (a Distribution Centre (DC)). The objective is twofold: to monitor the performance of different inventory control policies under distinct operative scenarios and to reduce the Internal Logistic Costs (ILCs) by investigating the effect of some critical parameters (i.e., the number of incoming/outgoing trucks from suppliers/to retailers, the number of forklifts and lift trucks, etc.) for increasing the service level provided to final retailers and allocating internal resources efficiently. To this end, a simulation model of a real DC is implemented.